Evolution of the major histocompatibility complex: isolation of class II A cDNA clones from the cartilaginous fish. - Kasahara, M (1992)
Along with the T-cell receptor and immunoglobulin, the major histocompatibility complex (MHC) plays a key role in mounting immune responses to foreign antigen. To gain insights into the evolution of the MHC, class II A cDNA clones were isolated from nurse sharks, a member of the class of cartilaginous fish. Two closely related cDNA clones, which might encode allelic products, were identified; of the three amino acid substitutions found in the alpha 1 domain, two were located at positions postulated to interact with processed peptides. The deduced nurse shark MHC class II alpha chains showed conspicuous structural similarity to their mammalian counterparts. Isolation of cDNA clones encoding typical MHC class II alpha chains was unexpected since no direct evidence for T-cell-mediated immune responses has been obtained in the cartilaginous fish. The cartilaginous fish is phylogenetically the most primitive class of vertebrates from which any MHC gene has been isolated.